2016
DOI: 10.1016/j.amjmed.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Influenza Vaccination and Missed Opportunities Among Adults with High-Risk Conditions, United States, 2013

Abstract: Background Since 1960, the Advisory Committee on Immunization Practices (ACIP) has recommended influenza vaccination for adults with certain high-risk conditions because of increased risk for complications from influenza infection. We assessed national influenza vaccination among persons 18-64 years with high-risk conditions. Methods We analyzed data from the 2012 and 2013 National Health Interview Survey (NHIS). The Kaplan-Meier survival analysis procedure was used to estimate the cumulative proportion of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
57
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 28 publications
10
57
1
Order By: Relevance
“…This study showed that age ≥50 years, having a college or higher education, and having high-risk conditions were significantly associated with influenza vaccination, consistent with other studies [25,26]. Reporting having visited a doctor or healthcare professional and having received a recommendation with or without offer for vaccination were significantly associated with influenza vaccination, suggesting that receiving a recommendation for vaccination from a healthcare provider plays an important role in early season influenza vaccine uptake, and an offer can increase the likelihood of vaccination uptake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed that age ≥50 years, having a college or higher education, and having high-risk conditions were significantly associated with influenza vaccination, consistent with other studies [25,26]. Reporting having visited a doctor or healthcare professional and having received a recommendation with or without offer for vaccination were significantly associated with influenza vaccination, suggesting that receiving a recommendation for vaccination from a healthcare provider plays an important role in early season influenza vaccine uptake, and an offer can increase the likelihood of vaccination uptake.…”
Section: Discussionsupporting
confidence: 92%
“…Increased influenza vaccination coverage among adult populations is needed. Strategies to increase vaccination coverage include assessment of patients’ vaccination indications by healthcare providers and routine recommendation and offer of needed vaccines to adults, implementation of client reminder-recall systems, and use of provider reminders for vaccination [22,2530]. …”
Section: Discussionmentioning
confidence: 99%
“…In one study, among unvaccinated high risk adults, 90 % reported at least one visit in which influenza vaccine could have been administered [25]. The regression analyses in this study supported those findings and indicated that reducing missed opportunities is a critical element in increasing influenza vaccination.…”
Section: Discussionsupporting
confidence: 78%
“…Preventive strategies against infection include vaccinations and anti‐microbial prophylaxis. Despite recommendations for vaccinations in high‐risk patients, such as those with SLE or receiving immunosuppressants, actual vaccination coverage remains low . Also, published studies often did not report the vaccination and anti‐microbial prophylaxis practices in their centres.…”
Section: Discussionmentioning
confidence: 99%